Protection And Legal Security System For Digital Signature Users As Consumers In The Indonesian Legal System - Rusli, Tami; Jainah, Zainab Ompu; B, Erlina (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to find legal protection against digital signature users as consumers associated with the principle of justice. This research uses a normative juridical approach by focusing on secondary data. The research specification used is descriptive-analytical. The research stages were carried out through library research and field research as support. Data collection techniques were carried out through document studies and interviews. While data analysis is carried out in a qualitative, juridical manner. The results showed that since the enactment of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE), the legal force and legal certainty of electronic information, electronic documents, and electronic signatures as valid evidence in electronic transactions such as e-commerce and e-business have the same legal force and legal certainty as the original. As a suggestion, in an effort to increase the effectiveness of the enactment of Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE), it is necessary to immediately issue a Government Regulation (PP) as an implementing regulation so as not to cause confusion for the community and, of course, the government itself in its law enforcement